Including Neuroscience in Social Work Education: Introducing Graduate Students to the Neurosequential Model of Therapeutics. Issue 4 (7th August 2020) - Mason, Christie; Kelly, Brian L.; McConchie, Virginia
ABSTRACT: To fill a gap in research on the incorporation of neuroscience in social work education, this article describes Master of Social Work (MSW) student and alumni experiences learning a neuroscience-informed model for practice with clients who have endured developmental trauma. The Neurosequential Model of Therapeutics (NMT) is a clinical decision-making tool that provides an estimate of how a client's current neurobiological functioning may have been impacted by trauma during the developmental period in order to inform the selection and sequencing of interventions. MSW students and alumni participated in focus groups exploring their perspectives on learning the NMT, the utility of the model in their work, and the fit between the model and social work theory and practice. Participants found the model helpful in conceptualizing client cases and applicable to their work, but challenging to implement due to others' lack of familiarity with the model, and insufficient infrastructure. These findings suggest the NMT may be a valuable tool for teaching neuroscience within schools of social work.